Highly Cross-Linked Polyethylene Reduces Wear and Revision Rates in Total Hip Arthroplasty: A 10-Year Double-Blinded Randomized Controlled Trial. (18th October 2017) - Devane, Peter A.; Horne, James Geoffrey; Ashmore, Alexander; Mutimer, Jonathon; Kim, Woosung; Stanley, James
Abstract : Background: Highly cross-linked polyethylene (XLPE) was developed to address the problem of wear and osteolysis associated with metal-on-conventional ultra-high molecular weight polyethylene (UHMWPE) bearing surfaces. The purpose of this study was to compare in vivo wear rates and clinical and radiographic outcomes between XLPE and UHMWPE in a prospective double-blinded randomized controlled trial with a minimum of 10 years of follow-up. Methods: We randomized 122 patients to receive either a conventional UHMWPE liner (Enduron; DePuy) or an XLPE liner (Marathon; DePuy). Ninety-one patients were assessed clinically and radiographically at a minimum of 10 years (range, 10.08 to 12.17 years). Oxford Hip Scores and Short Form-12 Health Survey scores were collected. The radiographs were analyzed for osteolysis and for 2-dimensional (2-D), 3-dimensional (3-D), and volumetric wear using validated software. Results: All 122 patients were accounted for at the 10-year follow-up evaluation. Twelve patients had undergone revision surgery, 21 patients had died (1 of whom had previously undergone revision surgery), and 2 patients were unable to return for follow-up, leaving 91 patients available for clinical and radiographic evaluation. At a minimum of 10 years, 3-D wear rates were significantly lower (p < 0.001) in the XLPE group (mean, 0.03 mm/yr) than in the conventional UHMWPE group (mean, 0.27 mm/yr). The prevalence of osteolysis was also significantly lower in the XLPE group (38% versus 8%, p < 0.005), as was the revision rate (14.6% versus 1.9%, p = 0.012), with 10 of the 12 revisions being in the Enduron group. There was no significant difference between the clinical scores of the 2 groups. Conclusions: XLPE liners have significantly reduced wear and are associated with a greater implant survival rate at 10 years compared with conventional UHMWPE liners. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.